COMPARISON OF DOPPLER INDICES BETWEEN OBSTRUCTED AND NON-OBSTRUCTED KIDNEY - Ilyas, Saira; Fiza Waseem,; Aun Bin Tariq,; Sara Shaukat,; Afzaal Mehmood, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute renal colic is a common acute urologic conditions often caused by urolithiasis. However, diagnosis of obstruction due to urolithiasis sometimes becomes difficult especially when there is an insufficient dilation of urinary tract proximal to obstruction. In these situations, intra renal artery doppler assessment may be utilized as a diagnostic modality. The aim of this study to evaluate intra-renal arterial Doppler parameters in patients presenting with unilateral acute renal colic, comparing obstructed and non-obstructed kidneys. Methods: This case controled study was done at Azeem Ultrasound and Xray Center and was completed in 6 months [12-12-2023 till 11-06-2024]. 60 individuals were included in the study. Pelvicalyceal system dilatation was examined in each kidney using USG images. For the evaluation of inter-lobar arteries, a minimum of 3 doppler spectra were taken, and their mean was calculated. Resistiv index (RI) was measured using the standard formula, and the mean RI value was determined for each kidney. Results: The resistive index was elevated in the obstructed group (0.72 ± 0.10) versus the unobstructed group (0.63 ± 0.07; p < 0.001). The predictive accuracy showed a sensitivity of 70.0%, a specificity of 86.67%, a postive pridictive value (PPV) of 78.97%, and an negatieve predictiev value (NPV) of 80.15%. Conclusion: The comparison of Doppler indices between obstructed and unobstructed kidneys in patients with urolithiasis reveals significant differences. Elevated RI and PI values, along with increased PSV, highlight that hemodynamics is altered in the presence of renal obstruction. These findings support the use of Doppler ultrasound as a valuable diagnostic tool, helping in the timely identification and management of obstructive uropathy.